Actividades físicas, deportivas y recreativas para el aprovechamiento del tiempo libre en los niños y niñas de 06-12 años del recinto Macuchi, parroquia La Esperanza, cantón Pujilí, provincia de Cotopaxi en el periodo 2012-2013 - Arias Valencia, Lisbeth Yajaira (2015)
This work talks about important topic issue of obesity and sedentary lifestyle that lies in children 06 to 12 years Macuchi Campus in the Parish of Hope. Since due to misuse of free time children are susceptible to these health problems, so we have seen the need to let them know about them both as parents, teachers and authorities of the sector importance of the proper use of leisure time occupation and healthy through the practice of physical, sports and recreational activities. Identified the problem that exists with children, the objective of this research focused on proposing a tutorial of games in which physical recreation, sports and developed based on the best use of leisure time and recreational satisfaction of children Macuchi enclosure….